Permeability Enhancement Technology for Soft and Low-Permeability Coal Seams Combined with Hydraulic Perforation and Hydraulic Fracturing - Zhengjie Shang; Zhaofeng Wang; Zhiheng Cheng; Hongbing Wang; Liang Chen; Lei Li; Jianhua Fu; Hao Liu (Geofluids)
The No. 21 coal seam in the Zhengzhou mining area is a soft, three-layer, low-permeability coal seam prone to outbursts. The three-layer structure includes the coal seam and the roof and floor layers, which exhibit high gas contents and poor permeability. The dynamic hazards caused by coal and gas outbursts are very serious. A new permeability-increasing fracturing technique that combines hydraulic perforation and hydraulic fracturing was developed specifically for the geologic conditions of the gas-bearing No. 21 coal seam. Numerical simulations were developed to study the influence of the technique on the stress distribution and permeability of the coal around the borehole. In addition, the extracted borehole gas concentrations and extraction amounts at multiple sites were investigated before and after using the technique. The study shows that the permeability-increasing fracturing technique destroys the concentrated stress coal pillars via the development of fractures between boreholes in exposed hydraulically perforated coal. The coal stress within the zone with an effective increase in permeability decreased by 30%. Furthermore, the permeability in this zone increased by three times, and the average extracted gas concentration increased by over six times. The gas pressure in the No. 21 coal seam decreased from 1.1 MPa to 0.4 MPa, and the gas content decreased from 15.96 m3/t to 5.6 m3/t. All outburst prediction indexes measured on site did not exceed their respective limits. The technique not only effectively eliminated the dynamic hazards caused by coal and gas outbursts but also achieved efficient gas extraction in the Zhengzhou mining area.